Activation of the hypothalamic-pituitary-adrenal stress axis induces cellular oxidative stress - Spiers, Jereme G.; Chen, Hsiao-Jou Cortina; Sernia, Conrad; Lavidis, Nickolas A. (Frontiers in Neuroscience, 2015)
Glucocorticoids released from the adrenal gland in response to stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis induce activity in the cellular reduction-oxidation (redox) system. The redox system is a ubiquitous chemical mechanism allowing the transfer of electrons between donor/acceptors and target molecules during oxidative phosphorylation while simultaneously maintaining the overall cellular environment in a reduced state. The objective of this review is to present an overview of the current literature discussing the link between HPA axis-derived glucocorticoids and increased oxidative stress, particularly focussing on the redox changes observed in the hippocampus following glucocorticoid exposure.